2023
DOI: 10.1073/pnas.2217891120
|View full text |Cite
|
Sign up to set email alerts
|

Prestin’s fast motor kinetics is essential for mammalian cochlear amplification

Abstract: Prestin (SLC26A5)-mediated voltage-driven elongations and contractions of sensory outer hair cells within the organ of Corti are essential for mammalian cochlear amplification. However, whether this electromotile activity directly contributes on a cycle-by-cycle basis is currently controversial. By restoring motor kinetics in a mouse model expressing a slowed prestin missense variant, this study provides experimental evidence acknowledging the importance of fast motor action to mammalian cochlear amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 61 publications
4
34
0
Order By: Relevance
“…Given the recessive nature of DFNB61-associated prestin variants and premature OHC loss found in prestin-KO mice, it is likely that loss-of-function underlies degeneration of OHCs expressing p.R130S prestin. The partially impaired membrane targeting of p.R130S prestin reported previously Takahashi et al, 2023), and further confirmed in this study, is in line with such a loss-of-function-based pathology. Since prestin belongs to the SLC26 anion transport family, it was speculated that OHC loss found in prestin-KO mice might be ascribed to the loss of prestin-mediated anion transport activity (Liberman et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Given the recessive nature of DFNB61-associated prestin variants and premature OHC loss found in prestin-KO mice, it is likely that loss-of-function underlies degeneration of OHCs expressing p.R130S prestin. The partially impaired membrane targeting of p.R130S prestin reported previously Takahashi et al, 2023), and further confirmed in this study, is in line with such a loss-of-function-based pathology. Since prestin belongs to the SLC26 anion transport family, it was speculated that OHC loss found in prestin-KO mice might be ascribed to the loss of prestin-mediated anion transport activity (Liberman et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Although OHC loss was minimal at weaning, by 6 weeks of age OHC loss was evident in cochleae from Slc26a5 R130S/− (Fig. 5) and exceeded that reported in Slc26a5 R130S/R130S (Takahashi et al, 2023).…”
Section: Distortion Product Otoacoustic Emissions Are Vastly Reduced ...mentioning
confidence: 50%
See 3 more Smart Citations